1996
DOI: 10.1046/j.1365-2559.1996.d01-483.x
|View full text |Cite
|
Sign up to set email alerts
|

Ductal (endometrioid) adenocarcinoma of the prostate: a clinicopathological study of 16 cases

Abstract: Sixteen cases of ductal (endometrioid) carcinoma of the prostate are presented. The tumour presents in elderly men (age range 65-87 years) with haematuria or obstructive symptoms. Serum prostate specific antigen may be normal or raised. On cytoscopy, there is often an exophytic lesion in the region of the verumontanum. Histologically, two variants are recognized: papillary and cribriform, of which there were eight cases each. Eight cases consisted of pure ductal carcinoma and seven were mixed, containing a var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(53 citation statements)
references
References 10 publications
(11 reference statements)
3
47
3
Order By: Relevance
“…Similar to acinar adenocarcinomas, almost all ductal adenocarcinomas express prostate-specific antigen and prostate-specific acid phosphatase. [15][16][17]20 Alpha-methylacyl CoA racemase (AMACR) expression has been detected in 58 to 100% of ductal adenocarcinomas. [22][23][24] Although a lower percentage of cases of ductal adenocarcinoma seem to express AMACR compared with acinar adenocarcinoma, it has not been established whether there are comparative quantitative differences in AMACR protein levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to acinar adenocarcinomas, almost all ductal adenocarcinomas express prostate-specific antigen and prostate-specific acid phosphatase. [15][16][17]20 Alpha-methylacyl CoA racemase (AMACR) expression has been detected in 58 to 100% of ductal adenocarcinomas. [22][23][24] Although a lower percentage of cases of ductal adenocarcinoma seem to express AMACR compared with acinar adenocarcinoma, it has not been established whether there are comparative quantitative differences in AMACR protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…Limited scale data do exist on comparative protein expression in ductal versus acinar adenocarcinoma, 7,12,[14][15][16][17][18][19][20][21][22][23][24][25] but comparative global gene expression profiling has not been performed. The aim of this study was to examine the gene expression profiles of ductal versus acinar adenocarcinoma to assess the molecular relatedness of ductal and acinar adenocarcinomas and to identify potential molecular differences that may explain the different histopathological features and disparate clinical behavior of ductal adenocarcinoma of the prostate.…”
mentioning
confidence: 99%
“…Ductal adenocarcinomas of the prostate typically stain positive for PSAP and PSA. 8 The majority of these cancers present with high grade features and a primary Gleason pattern of 4, although patterns of 3 and 5 may also be seen. 9 A retrospective study of 108 patients by Tu et al 10 including patients undergoing radical prostatectomy for ductal adenocarcinoma of the prostate demonstrated that patients with pure ductal adenocarcinoma had shorter time to local recurrence (2.8 vs 4.9 years) but longer median OS (13.8 vs 8.9 years) than patients with mixed ductal adenocarcinomas after surgery.…”
Section: Seer Analysis Of Rare Prostate Cancer Variants Dm Marcus Et Almentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12] It can be identified as a lesser pattern in up to 3% of cases. Initially, these tumors were believed to be of endometrial origin arising in the verumontanum, a mĆ¼ llerian remnant; 4,5 however, it is now recognized that these are of prostatic epithelial origin.…”
Section: Prostatic Ductal Adenocarcinomamentioning
confidence: 99%
“…Initially, these tumors were believed to be of endometrial origin arising in the verumontanum, a mĆ¼ llerian remnant; 4,5 however, it is now recognized that these are of prostatic epithelial origin. [6][7][8][9][10][11][12] The concept of ductal adenocarcinoma as a specific entity has been challenged, most recently by Bock and Bostwick. 13 In a study utilizing LOH analysis of 12 polymorphic microsatellite markers, frequently lost in prostate cancer, Dawkins et al 14 reported LOH in none of the Gleason grade 3 tumors studied, 9% of high-grade prostatic intraepithelial neoplasia (HGPIN) lesions, 29% of Gleason grade 4 cancers and 60% of ductal adenocarcinomas, suggesting that these are in fact a different lesion.…”
Section: Prostatic Ductal Adenocarcinomamentioning
confidence: 99%